The effect of vitamin D3 supplementation accompanied by self-care on its serum level in lactating mothers: A randomizes clinical trial - Maryam Modarres; Roghieh Faraji; Fatemeh RahimiKian (Mashhad University of Medical Sciences, 2021)
Introduction: Due to the high prevalence of vitamin D deficiency, especially in lactating women and the importance of self-care of these mothers to ensure adequate concentration of vitamin D, this study was performed with aim to determine the effect of vitamin D supplementation with self-care on its serum level in lactating mothers. Methods: This randomized clinical trial study was performed in 2019 on 70 lactating mothers with serum vitamin D deficiency (D3 <30 ng / mL) referred to the health centers in Takab city. Concentration of 25OHvit. D3 Serum of all mothers was measured twice at baseline and 3 months after the end of intervention. By block randomization sampling method, the subjects were divided into two groups of 35 people (experimental and control). Self-care training was conducted for the intervention group in 4 sessions, with 7 days interval, in face to face form and telephone follow-up. Data were analyzed by SPSS software (version 16) and independent t-test and Mann-Whitney test. P<0.05 was considered statistically significant. Results: The two groups were homogeneous in demographic variables before the intervention. There was significant increase in vitamin D3 concentration in the intervention group compared to the control group after self-care training (p <0.001). Conclusion: In addition to prescribing a vitamin D-rich diet to lactating mothers, sels-care and psychological induction of self-care behaviors are effective in taking vitamin D supplements in breastfeeding mothers.